Ethical Considerations in AI: Navigating the Complexities of Bias and Accountability - Islam, Md.Mafiqul (Journal of Artificial Intelligence General science (JAIGS) ISSN:3006-4023, 2024)
Ethical considerations in artificial intelligence (AI) have become increasingly crucial as AI technologies permeate various aspects of society. This paper delves into the complexities surrounding bias and accountability in AI systems. Bias in AI algorithms can perpetuate societal inequalities and discrimination, while accountability gaps raise concerns about the responsible use of AI and potential legal liabilities. By exploring these issues, this paper aims to shed light on the ethical challenges inherent in AI development and deployment, offering insights into how stakeholders can navigate these complexities to foster more equitable and responsible AI applications.